Monitoring and Commitment in Bank Lending Behavior - Blavy, Rodolphe (IMF Working Papers; Working Paper, 2005)
The paper proposes a theoretical argument on the nature of bank lending, based on the idea that, through commitment and monitoring, banks overcome basic informational asymmetries with borrowers. By bringing together loan commitment theories and credit rationing theories, the paper shows that, within a framework of asymmetric information between lenders and borrowers and under costly termination of lending arrangements, commitment may explain the accumulation of nonperforming loans by banks. Two additional results follow: (i) that banks favor borrowers with well-known production functions and long-term credit history; and (ii) that interest rate spreads may be large if significant market imperfections prevail.